Cross-Sectional Study of Sexual Behavior, Alcohol Use, and Mental Health Conditions Associated With Sexually Transmitted Infections Among Deploying Shipboard US Military Personnel. Issue 11 (20th April 2019) - Harbertson, Judith; Scott, Paul T; Lemus, Hector; Michael, Nelson L; Hale, Braden R
Abstract: Introduction: Limited comprehensive data exist on risk behavior associated with sexually transmitted infections (STI) among ship-assigned US military personnel during the predeployment time period (PDT). This study examined whether sexual risk behaviors, alcohol use, involuntary drug consumption (IDC), posttraumatic stress disorder (PTSD), and depression during the 12 months prior to deployment were associated with provider-diagnosed STIs in this population. Materials and Methods: Using cross-sectional data collected during 2012–2014 among sexually active personnel, multivariable regression assessed factors associated with STIs among all men ( n = 1, 831). Stratified analyses were conducted among men who have sex with women (MSW, n = 1, 530), men who have sex with men or men and women (MSM, n = 83), and excluded those not reporting sexual partner gender ( n = 218). Results: Among MSW, transactional sex (AOR 3.8, 95% CI 1.5–9.4) meeting sexual partners at work (AOR 4.3, 95% CI 2.0–9.2), IDC (AOR 6.6, 95% CI 3.0–14.5), and incomplete mental health assessments (AOR 4.4, 95% CI 1.6–12.0) were significantly associated with STIs after adjustment. Among all men, those who identified as MSM (AOR 4.6, 95% CI 1.9–11.2) and drug screen positive (AOR 3.3, 95% CI 1.3–8.6) were significantly more likely to report an STI. Conclusions: Previously unreported factors significantly associated with STIs at the PDT among MSW in the adjusted analysis were meeting sexual partners at work and IDC. IDC during the PDT warrants further exploration. These results can inform tailored STI reduction interventions among shipboard personnel and similarly aged civilians undergoing similar transition/travel experiences.